Landscape genetics of Mexican biodiversity: A review - Rico, Yessica (Acta Universitaria, 2019)
The rich biodiversity of Mexico is threatened due to habitat fragmentation and climate change. Landscape genetics provides an excellent framework that integrates genetic, geographic, and ecological landscape data to inform conservation strategies. To discuss the value of landscape genetics for the study of the Mexican biota, a literature review of landscape genetics studies in Mexico was conducted to highlight trends of taxonomic groups, habitats, and research objectives. A total of 20 studies were identified: 65% in plants and 35% in animals. A large proportion of studies focused on temperate ecosystems and tropical forests, whereas marine and urban environments were lacking. Detection of linear barriers and landscape features on gene flow were the most popular objectives, while two objectives were exclusive to plants: spatial adaptive variation and estimates of contemporary gene flow with parentage analyses to evaluate effects of habitat fragmentation. Potential areas of research for landscape genetics studies in Mexico and recommendations are discussed.